A Decision Support System Of Teacher Recruitment Using Simple Additive Weighting Method At Al Fida Foundation Bengkulu - Laida, Risa; Maryaningsih, Maryaningsih; Julita , Rina (Jurnal Komputer Indonesia, 2022)
The teacher is the most decisive part in the education system. The difficulty of recruiting teachers is a challenge for the Al Fida foundation, where the selection process starts from a written test, a reading test of the Qur'an, microteaching and interviews. To simplify the process, a system is needed to solve these problems using Simple Additive Weighting which is used to rank prospective teachers with the same characteristics which can then be used as consideration in making policies. The results of the application of the Simple Additive Weighting method can be used by the AL-Fida foundation in recruiting teachers based on the ranking results according to the large number of prospective teachers.